PENYULUHAN KEBERSIHAN LINGKUNGAN SEKOLAH UNTUK MENINGKATKAN PENGETAHUAN PADA SISWA SDN TERUSAN 1 INDRAMAYU - Sarinah Basri K (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2019)
Health education has the purpose of changing or influencing human behavior individually, in groups and communities to be more independent in achieving the goals of healthy living. In this health education method is needed so that the delivery of messages can be as expected. Submission of methods in counseling is to use lectures, videos, and actions on environmental cleanliness. With this activity students are expected to be able to increase knowledge of the cleanliness of the school environment such as disposing of garbage in its place, being able to distinguish organic and inorganic waste, not scribbling walls and tables and consciously wanting to work together to clean the yard and classrooms. The implementation of service requires the collaboration of various parties so that health education can be done not only once, but it is conducted routinely to monitor the development of students' knowledge regarding environmental hygienein schools. In addition to lectures, videos and actions, the application or delivery of health education can also use educational media games because with game media students can more easily understand, students also do not experience boredom in delivering material.